THE PSYCHOLOGICAL VIEWS OF THE MEDIEVAL ARMENIAN PHILOSOPHER GRIGOR TATEVATSI - Zakaryan, Seyran (Modern Psychology, 2023)
The article analyzes the psychological views of the famous medieval Armenian theologian-philosopher Saint Grigor Tatevatsi (1346-1409). The purpose of the article is to show the attitude of the Armenian thinker regarding the human nature, the relationship between the soul and the body, the composition of the soul, its types and powers. According to the author, Tatevatsi, as a scholastic thinker, strives to synthesize the theological and philosophical propositions during the discussion of various issues, including those related to the soul. On the one hand, Tatevatsi rejects the Platonic views that identify man with his soul and the materialistic view that represents man as only a body, and on the other hand, the dualistic view that represents man as having two separate natures. Man is a unity of soul and body, and although they are different in their nature, properties and roles, they form single human nature. Although he gives priority to the soul, he believes that a person is perfect with the unity of the soul and the body and the relationship between the soul and the body should be based on the principle of justice. Tatevatsi, opposed to the extreme viewpoints (platonic, ascetic) regarding the valuation of the soul and body, which consider the body as the cause of sin and evil, defends the Aristotelian approach of the unity of the soul and the body, which means the actual recognition of the "rights" of the body and its importance  role in the salvation of man.
Keywords: Grigor Tatevatsi; psychology; soul; body; principle of justice; vegetal, sensual and rational parts of the soul; powers of the soul; rational and irrational parts of the soul